PLGA scaffold combined with MSCs transplantation improved neural function and brain tissue structure in rats with traumatic brain injury - Na Xu; Zihuan Sun; Weikang Guan; Yiming Liu; Yun Gao; Chaoxian Yang (Brain Research Bulletin)
Poly (lactic-co-glycolic acid) (PLGA) is an important biomaterial for tissue defect repair, but its application in replacing missing brain tissue needs improvement. Mesenchymal stem cells (MSCs) have been used to treat various neurological diseases, but they face challenges when filling large tissue defects. The purpose of this study was to investigate the effects of PLGA combined with MSCs transplantation on brain structure and neural function in rats with traumatic brain injury (TBI), and explore its possible mechanism. The results showed that both PLGA transplantation and PLGA+MSCs transplantation could improve the brain structure and promote nerve function recovery in rats with TBI, with PLGA+MSCs transplantation being superior to PLGA transplantation. Furthermore, compared to PLGA transplantation alone, PLGA+MSCs transplantation further reduced brain injury and cell apoptosis, promoted neuron survival, and improved synaptic plasticity. Overall, the adhesion of MSCs to PLGA can enhance the therapeutic efficacy of PLGA in rats following TBI.